PRODUCTIVE ZAKAT AS A FINANCIAL INSTRUMENT IN ECONOMIC EMPOWERMENT IN INDONESIA: A LITERATURE STUDY - Ismail, Ismail; Gea, Dalmaisyah; Shabri Abd. Majid, M.; Marliyah, Marliyah; Handayani, Rita (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The Muslim population who has great potential in tithing is Indonesia. As the largest Muslim country in Asia, one of the financial instruments that should be appreciated is productive zakat. This program can not only help underprivileged people but also can make people who have been lacking in the economy and have always been recipients of zakat can change their positions into muzakki. This study describes the extent of research on productive zakat and its empowerment in Indonesia by obtaining the results of 375 published articles that have been eliminated according to search data from 2017 to 2021. Besides that, it also shows that productive zakat is very great in playing its role as one of the Islamic financial instruments in Indonesia in empowering and alleviating poverty through philanthropic institutions that shelter it.